Fixation with lower limb immobilization in primary and secondary exstrophy closure: A saving grace. Issue 2 (April 2023) - Haffar, Ahmad; Morrill, Christian; Crigger, Chad; Sponseller, Paul D.; Gearhart, John P.
Summary: Purpose: A pivotal factor in the success of bladder closure in patients with classic bladder exstrophy (CBE) is the postoperative immobilization of the pelvis and lower extremities after pelvic osteotomy. This study investigates the outcomes of closure among patients with lower limb immobilization using many techniques. The authors hypothesize that the addition of external fixation (pelvic immobilization) in patients with any form of limb immobilization will be associated with improved outcomes. Methods: A prospectively maintained institutional exstrophy–epispadias complex database of 1415 patients was reviewed for patients with CBE who had undergone closure with available immobilization and osteotomy data. Association between closure outcomes and immobilization techniques were determined. Univariate analysis was performed using Chi-Square or Fischer–Exact test as appropriate for categorical variables. Multivariate analysis via binomial logistic regression was used to identify factors leading to successful closure. Results: A total of 747 closure events matching the inclusion criteria were identified. Patients included 508 males and 239 females. There were 597 primary closures (79.9%) with 150 reclosure events (20.1%). Limb immobilization was used in 627 (83.9%) of closure events. Successful closures were associated with osteotomy use (p < 0.0001) and limb immobilization (p < 0.0001); specifically, the combined anterior innominate with posterior vertical iliac osteotomy and modified Buck's traction with external fixation (p < 0.0001, p < 0.0001). Among the group of 33 patients who received external fixation alone and no other type of immobilization, the failure rate was 33.3%, comparatively, patients with any form of combined immobilization (external fixation with lower limb immobilization) had a failure rate of 7.1% ( Table 1). Among patients immobilized with mummy wrap, spica casting, or knee immobilizers, external fixation was associated with 3.76 increased odds of successful closure (p = 0.0005, 95% CI 1.79–7.90). In a unique group of 67 patients without pelvic osteotomy or any form of pelvic or limb immobilization, the failure rate was 74.6%. Discussion: This study confirms, in a larger series, previous findings of improved outcomes when patients are immobilized with modified Buck's traction and external fixation. The authors apply this technique in most all closures and recommend this technique be utilized whenever feasible. However, regardless of the manner of lower limb immobilization, external fixation is a critical factor to optimize closures and ensure success. Conclusion: The results of this study clearly suggest the use of external fixation can be protective against bladder closure failure. The use of pelvic immobilization, in addition to post-operative lower limb immobilization should be strongly considered. Summary Table 1 Failure rate among all closures (to be used in the extended summary if possible). Summary Table 1 Total closures Closures with osteotomy Closures without osteotomy Method of Immobilization Total no. (n = 597) No. failed % Failed Total no. (n = 411) No. failed % Failed Total no. (n = 186) No. failed % Failed External fixation with no lower limb immobilization 33 11 33.3 31 10 32.3 2 1 50 External fixation with any form of lower limb immobilization 184 13 7.1 174 11 6.3 10 2 20 External fixation with spica casting/mummy wrapping 42 14 33.3 39 12 30.8 3 2 67 Spica casting with no external fixation 148 81 54.7 74 30 40.5 74 51 68.9 No form of Immobilization 87 60 69.0 20 10 50 67 50 74.6